Sulfonation of poly(p-phenylenediamine) polymer. Issue 1 (1st January 2017) - Amer, Ismael
Abstract: The sulfonation of poly( p -phenylenediamine) (P( p PD)) polymer was accomplished by oxidative copolymerization of p -phenylenediamine ( p PD) with 2, 5-diaminobenzenesulfonic acid (DABSA) and 2-aminobenzenesulfonic acid (2ABSA) monomers with 50/50 mol% ratios, using ammonium persulfate ((NH4 )2 S2 O8 ) as an oxidant. The p PD-co-DABSA and p PD-co-3ABSA copolymers obtained were fully characterized and compared by Fourier transform infrared spectroscopy (FT-IR), 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR), Gel permeation chromatography (GPC), Wide-angle X-ray diffraction (WAXD) and Thermogravimetric analysis (TGA). The yield, molecular weight, solubility, degree of sulfonation, molecular structure and thermal stability of the copolymers were shown to be dependent on the type of comonomer. The solubility of p PD-co-DABSA and p PD-co-2ABSA copolymers was significantly improved compared to the P( p PD) polymer in most solvents. Conversely, the yield and molecular weight values obtained for the p PD-co-DABSA and p PD-co-2ABSA copolymers were lower than those obtained for P( p PD) polymer. The TGA results showed that P( p PD), p PD-co-DABSA and p PD-co-2ABSA copolymers have good thermal stability and decompose above 200°C in nitrogen.